Kintamani Tourism Destinations: A Study Of Tourist Perceptions Milenial Generation - Prasiasa, Dewa Putu Oka; Widari, Dewa Ayu Diyah Sri (Politeknik Internasional Bali, 2023)
The purpose of this study is to examine the perceptions of the millennial generation towards Kintamani as a tourism destination from three aspects, namely attractions, facilities and accessibility. As a qualitative research, data analysis was carried out in a qualitative descriptive manner. The sample of this study was 99 people, determined by the Slovin method, consisting of 89 millennial generation domestic tourists and 11 millennial generation foreign tourists. The results showed that Kintamani Tourism Destinations for attractions were considered very good with an average value of 4.46; facilities are considered good with an average value of 3.67; and accessibility is considered good with an average value of 3.91. This study also recommends the need to improve the quality and quantity of supporting facilities for the Kintamani Tourism Destination such as tourism information centers, public toilets, street lighting, money changers, parking lots, and the quality of roads in the Kintamani Tourism Destination area.